Factors Inhibiting Economic Growth of The Community In West Nusa Tenggara Province - Febrianti, Nadia; Hailuddin, Hailuddin (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the factors inhibiting community economic growth in West Nusa Tenggara Province. Based on statistical news from the Central Bureau of Statistics of NTB Province, the low human development index, high poverty rate and open unemployment rate can potentially be a factor inhibiting the economic growth of the community in West Nusa Tenggara Province. This research uses quantitative descriptive method with multiple linear regression analysis tools panel data with Fixed Effect Model (FEM) approach. The data used in this study are secondary data from 2019-2023 for districts / cities in West Nusa Tenggara Province. The independent variables in this study are Human Development Index (HDI), Poverty Level and Open Unemployment Rate while the dependent variable is GRDP. The results showed that the poverty rate and the open unemployment rate had a negative but insignificant effect on GRDP so that these two variables had the potential to inhibit economic growth in NTB Province. While the human development index variable has a positive and significant effect on GRDP, meaning that HDI has no potential as an obstacle to economic growth in West Nusa Tenggara Province